Meggs' History of Graphic Design - Philip B. Meggs; Alston W. Purvis (New Jersey Wiley & Sons, Inc., 2016)
The bestselling graphic design reference, updated for the digital age Meggs' History of Graphic Design is the industry's unparalleled, award-winning reference. With over 1,400 high-quality images throughout, this visually stunning text guides you through a saga of artistic innovators, breakthrough technologies, and groundbreaking developments that define the graphic design field. The initial publication of this book was heralded as a publishing landmark, and author Philip B. Meggs is credited with significantly shaping the academic field of graphic design. Meggs presents compelling, comprehensive information enclosed in an exquisite visual format. The text includes classic topics such as the invention of writing and alphabets, the origins of printing and typography, and the advent of postmodern design. This new sixth edition has also been updated to provide: The latest key developments in web, multimedia, and interactive design Expanded coverage of design in Asia and the Middle East Emerging design trends and technologies Timelines framed in a broader historical context to help you better understand the evolution of contemporary graphic design Extensive ancillary materials including an instructor's manual, expanded image identification banks, flashcards, and quizzes You can't master a field without knowing the history. Meggs' History of Graphic Design presents an all-inclusive, visually spectacular arrangement of graphic design knowledge for students and professionals. Learn the milestones, developments, and pioneers of the trade so that you can shape the future.
Keywords: Nonfiction; Art; Design